2019
DOI: 10.1159/000500415
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Quadriceps Muscle Thickness with Motor Paralysis and Muscle Echo Intensity in Post-Stroke Patients

Abstract: Introduction: Quadriceps muscle atrophy and quality loss, defined as an increased ratio of intramuscular fat and/or connective tissue, are often observed especially in the paretic limb of post-stroke patients. This study was performed to examine the relationship of quadriceps muscle thickness (MT) with muscle echo intensity (EI) and the severity of motor paralysis after stroke. Methods: Thirty-six hemiparetic subacute post-stroke patients were enrolled. We examined the MT (index of muscle quantity) and the EI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
3
5
0
Order By: Relevance
“…In the stepwise regression analysis, MT of the QF was extracted to predict EI of the QF in both Japanese and Brazilian participants. The same relationship was found in a simple regression analysis in the present study (Table 4), and similar findings were demonstrated in previous studies on older individuals [5,28] and stroke patients [30]. In support of this relationship, the EIs were significantly correlated with LBM in both Japanese and Brazilian participants, suggesting that muscle size is a strong predictor of EI in older individuals.…”
Section: Plos Onesupporting
confidence: 93%
See 1 more Smart Citation
“…In the stepwise regression analysis, MT of the QF was extracted to predict EI of the QF in both Japanese and Brazilian participants. The same relationship was found in a simple regression analysis in the present study (Table 4), and similar findings were demonstrated in previous studies on older individuals [5,28] and stroke patients [30]. In support of this relationship, the EIs were significantly correlated with LBM in both Japanese and Brazilian participants, suggesting that muscle size is a strong predictor of EI in older individuals.…”
Section: Plos Onesupporting
confidence: 93%
“…The EIs of the RF, VL, and QF in the present study were inversely correlated with the MTs (Table 3), consistent with some previous studies [5,29,30]. Fukumoto et al [28] also reported that EI of the QF was negatively correlated with MT of the QF (r = -0.33, P < 0.01).…”
Section: Plos Onesupporting
confidence: 92%
“…Previous studies have reported that there is a significant negative association between MT and EI on quadriceps femoris in healthy older adults 19,29 ) . A previous study of acute stroke patients by Maeda et al reported a significant negative association between MT and EI of the quadriceps femoris 30) . These previous findings suggest that quantitative and qualitative changes of individual muscles are associated with each other.…”
Section: Discussionmentioning
confidence: 82%
“…A single examiner (H.M.) with extensive training in US measurement conducted all measurements. It was reported that the intraclass correlation coefficients (1, 1) of MT and RF EI were 0.98 and 0.94, respectively (n = 13, 26 limbs) [20].…”
Section: Ultrasonographic Assessmentmentioning
confidence: 93%